A curated harvesting approach to establishing a multi-protocol online subject portal - Sanderson, Robert; Harrison, John; Llewellyn, Clare (International Conference on Digital Libraries: Proceedings of the 6th ACM/IEEE-CS joint conference on Digital libraries; 11-15 June 2006, 2006)
We describe a curated harvesting approach to creating and maintaining a subject portal, comprising selected records harvested from remote services via information retrieval standards such as SRU, Z39.50 and OAI-PMH. The result was a web-based data curation interface where administrative users can configure access to remote resources, queries to be performed at them, and review records for inclusion in end user searches.